Evaluating relapse prophylaxis in addition to interdisciplinary multimodal pain therapy for back pain: a randomised controlled trial - Julia Schmetsdorf; Kathrin Krüger; Jacqueline Posselt; Runde Werner; Hans-Georg Zechel; Thomas Kohlmann; Christian Krauth (Journal of Rehabilitation Medicine)
Objective: This study aimed to evaluate the effectiveness of a 12-month relapse prophylaxis following a 4-week interdisciplinary multimodal pain therapy approach for patients with back pain. The study examined whether the intervention reduced days of incapacity to work (primary outcome) and improved functional capacity and health-related quality of life (secondary outcomes) compared with interdisciplinary multimodal pain therapy alone.